1993
DOI: 10.1557/proc-325-401
|View full text |Cite
|
Sign up to set email alerts
|

Clusters and the Nature of Superconductivity in Ltmbe-GaAs

Abstract: The structure and properties of GaAs layers grown by molecular-beam epitaxy at low temperature (150-250 °C) have been studied. The samples were found to contain up to 1.5 at.% extra As, which formed nano-scale clusters under annealing. The dependences of the excessive As concentration and As-cluster size and density on the growth and annealing conditions were established. LT-GaAs layers were found to have high electrical resistivity, however, our investigations of microwave absorption in a weak magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
5

Year Published

1998
1998
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 8 publications
1
35
0
5
Order By: Relevance
“…3, the perpendicular lattice mismatch increases with decreasing growth temperature as the excess As concentration does. Note, however, that the lattice mismatches of the LT grown InAs samples are smaller by almost one order of magnitude than those of LT grown GaAs samples [2][3][4][5][6][7]. For LT grown GaAs, Liu et al [4] deduced the relation of ∆a⊥/a = 1.24×10…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3, the perpendicular lattice mismatch increases with decreasing growth temperature as the excess As concentration does. Note, however, that the lattice mismatches of the LT grown InAs samples are smaller by almost one order of magnitude than those of LT grown GaAs samples [2][3][4][5][6][7]. For LT grown GaAs, Liu et al [4] deduced the relation of ∆a⊥/a = 1.24×10…”
Section: Methodsmentioning
confidence: 99%
“…Among those studies, Docter et al [1] have demonstrated that as low as 0.1 % of excess As in LT grown GaAs can be detected by means of secondary ion mass spectroscopy (SIMS). The effect of the excess As to the lattice spacing in LT grown GaAs has been investigated in several studies [2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…The grains have an average size of ~100 nm and are extended along one direction. As the growth temperature increases, the grain size dereases down to 3-5 nm at Т g = 250°С) [6].…”
Section: Growth-surface Structurementioning
confidence: 99%
“…It was shown that a decrease in the growth temperature from conventional values of 500-600°С down to 150-200°С results in the incorporation of excess non-stoichiometric arsenic into the lattice mainly in the form of point defects [1][2][3][4][5][6]. LT-GaAs containing excess arsenic possesses unique physical properties such as high specific resistance (up to 10 8 Ω⋅cm) and a very low lifetime of minority charge carriers (<1 ps).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation